Kajian Sistematis atas Stimulus–Organism–Response (S-O-R) dalam Pemasaran Digital Syariah - Fahrudin Misdar; Nandang Ikhwanudin; Panji Adam (ITB AAS INDONESIA Surakarta, 2026)
This systematic literature review integrates various empirical data at the intersection of the Stimulus-Organism-Response (S-O-R) framework, digital marketing strategies, and Islamic ethical principles. This study aims to construct an integrated model through a careful data screening process from the Google Scholar database for the period 2021 to 2025. The research procedure was carried out by referring to the PRISMA guidelines, resulting in a final sample of 21 high-quality empirical articles. The thematic analysis successfully identified contrasting differences in the classification of stimuli driving Islamic digital marketing, namely between digital triggers such as content quality and social engagement, and product cues primarily represented by halal certification. These external stimuli activate two specific internal processes within consumers, namely cognitive mechanisms guided by halal awareness and emotional dimensions driven by religious awareness. Although purchase intention is confirmed as the main behavioral metric, this analysis also finds a growing trend of impulsive buying in an information-dense digital environment. As a result, this study formulates the Master S-O-R Model, which views Islam not merely as a cultural backdrop but as an active psychological filter for consumers within the current algorithmic trading ecosystem.